Evaluation of hazardous wastes generated from automotive industry in turkey and their disposal methods - Yazıcı, Burcu (My University, 2011)
TÜRKİYE’DE OTOMOTİV SANAYİNDEN KAYNAKLANAN TEHLİKELİ ATIKLARIN VE BERTARAF YÖNTEMLERİNİN İNCELENMESİ Tehlikeli atıklar toksisite, aşındırıcılık, tutuşabilirlik ve reaktivite gibi özellikleri sebebiyle insan sağlına ve çevreye olumsuz etkileri olan atıklardır. Tehlikeli atıkların kaynağı çeşitli endüstriyel, ticari, tarımsal ve hatta evsel faaliyetler olabilir. Bu çalışmada, Türk otomotiv endüstrisi kaynaklı tehlikeli atık üretimi incelenmiştir. Araç başına oluşan her bir tehlikeli atık için tehlikeli atık üretim faktörü hesaplanmıştır. Tehlikeli atık faktörünün belirlenmesi tehlikeli atık üretim rakamları ile üretilen tehlikeli atık miktarları arasındaki ilişkiyi kurabilmek için önemli bir araçtır. Tehlikeli atık faktörlerinin bilinmesi uzun vadeli tahminler yapılabilmesine yardımcı olur. Tehlikeli atık faktörü üreticilerden elde edilen tehlikeli atık miktarları ve üretim rakamları ile hesaplanmaktadır. Tehlikeli atık üretim faktörü otomobil, otobüs ve kamyon üreticileri için ayrı ayrı hesaplanmıştır. Her bir üretici için hesaplanan tehlikeli atık faktörleri kıyaslandığında, benzer prosesler uygulandığı halde araç yüzey alanı ve üretim rakamlarının artmasına bağlı olarak hesaplanan tehlikeli atık üretim faktörlerinde farklılıklar gözlemlenmiştir. Üretim proseslerindeki farklılıklar oluşan tehlikeli atığın tipini ve miktarını etkilemektedir. Yüzey hazırlama ünitelerinin uygulanması üretilen tehlikeli atık türlerine etkisi olduğu gibi atık faktörünü de önemli oranda etkiler. Örneğin; yüzey hazırlama ünitelerinde atık olarak fosfatlama çamuru oluşmaktadır. Bunun yanı sıra, bazı nanoteknolojik yüzey hazırlama prosesleri fosfatlama çamurunun oluşumunu tamamen engelleyebilir. Farklı üç tip motorlu kara taşıtı üretiminden kaynaklanan tehlikeli atık üretim faktörleri karşılaştırıldığında, otobüs üretimi için hesaplanan atık faktörü değerinin en fazla olduğu tespit edilmiştir. Üretim rakamlarındaki fazlalık ve küçük yüzey alanlarından dolayı, otomobil üretimi için hesaplanan tehlikeli atık faktörünün üç tip moyotlu kara taşıtı içinde en düşük değere sahip oluştuğu gözlemlenmiştir. Daha önceki çalışmalarda da değinildiği gibi oluşan tehlikeli atık miktarı üretim adedi ile doğru orantılıdır. 2010 yılında tespit edilen tehlikeli atık miktarı, üretime bağlı olarak 2009 yılı atık miktarlarına göre %20’lik bir artış göstermiştir.

EVALUATION OF HAZARDOUS WASTES GENERATED FROM AUTOMOTIVE INDUSTRY IN TURKEY AND THEIR DISPOSAL METHODS Hazardous wastes are wastes that jeopardize human health or environment due to their features such as toxicity, corrosivity, ignitability or reactivity. Hazardous wastes are produced from several industrial, commercial, agricultural or even from domestic activities. In this study, hazardous waste generation from Turkish automotive industry was evaluated. Hazardous waste generation factors per motor vehicle were calculated for each hazardous waste generated from automotive manufacturing. Determining the hazardous waste generation factors is an important tool while making a relationship between the production figures and the amount of generated hazardous waste. Long term predictions may be possible if the relative hazardous waste generation factors are accurately known. Hazardous waste generation factors were calculated by obtaining the generated hazardous waste amounts and the production figures from the facilities. Hazardous waste generation factors were calculated for each waste generated by the manufacture of three types of motor vehicles which are automobile, bus and truck. When the hazardous waste generation from the manufacture of these motor vehicles was compared, it was observed that hazardous waste generation factors for most of the waste types increased with increasing surface area of the vehicle and increasing production figures although similar manufacturing processes were applied. Differences in the manufacturing processes affect the type and quantity of the hazardous waste generated per production of a motor vehicle. It was observed that application of a surface treatment unit has a pronounced effect on hazardous waste generation factors and as well as the types of generated wastes. For instance, phosphating sludge will not be generated, if the facility does not apply surface treatment. Furthermore, some nanotechnological surface treatment processes may completely eliminate the generation of phosphating sludge. When hazardous waste generation factors of three types of motor vehicles are compared, bus manufacturing has the highest values. Due to relatively high production figures and small surface area, automobile manufacturing has the lowest hazardous waste generation factors. As it is mentioned before, hazardous waste generation increases in parallel with the production. There is approximately a 20% increase in the total amount of hazardous waste generated by the automotive industry from 2009 to 2010. This is in accordance with the increase in the production figures. In addition to the determination of hazardous waste generation factors, possible recycle/ recovery or disposal practices for the generated wastes were also examined. According to the declerations made by the automotive industry via the Hazardous Waste Declaration System, it was observed there is an increasing trend of recycling of generated hazardous wastes. While the recycling ratio was 65% in 2008, this ratio increased to 87% in 2010. Currently, energy recovery and incineration are commonly applied recycle/ recovery or disposal methods to the generated hazardous wastes.
Keywords: Atık Yönetimi; Otomotiv